TINJAUAN YURIDIS TERHADAP PENIPUAN HAK MILIK ATAS TANAH YANG DILAKUKAN OLEH MAFIA TANAH BERDASARKAN PASAL 378 KITAB UNDANG-UNDANG HUKUM PIDANA - Sang Ayu Made Ary Kusumawardhani, S.H., M.H. (VYAVAHARA DUTA, 2024)
The term criminal act comes from a term known in criminal law, namely strafbaarfeit. Even though this term is found in the Dutch WvS, there is no official explanation regarding the translation of the term "strafbaar feit". Strafbaar feit, a legal term in Dutch, is a series of the words "strafbaar" and the word "feit". "Strafbaar" means "can be punished" while "feit" means part of a reality. So literally the meaning of "strafbaar feit" is part of a reality that can be punished. The literal meaning is that what can be punished is the individual person. Ownership rights to land carried out by the land mafia can be analyzed from the perspective of Indonesian criminal law, especially in Article 378 of the Criminal Code (KUHP) which regulates fraud. This phenomenon often occurs during land buying and selling transactions by providing incorrect information. The formulation of the problem is how to review the juridical review of land ownership fraud committed by the land mafia based on article 378 of the criminal code and what is the legal basis for criminal acts of fraud committed by the land mafia. This type of research is normative legal research which departs from the vagueness of norms (vague norms) which are contained in the provisions of article 378 of the criminal code, regarding fraud, the meaning of the phrase deception. This research uses a conceptual approach, a statutory approach, and a case approach. The results of research on the Juridical Review of Land Ownership Fraud Committed by the Land Mafia Based on Article 378 of the Criminal Code, in this case the phrase deception which creates a blurring of norms. Legal basis for criminal acts of fraud committed by the land mafia. Acts of fraud committed by the mafia are very serious legal violations and can be charged under various laws in force in Indonesia, including: Article 263 paragraph (1), article 378 of the code of law. criminal law (KUHP), legal protection in cases of fraud committed by the land mafia is still far from perfect. Victims often experience difficulty in obtaining adequate protectio